Navigating cross-cultural classrooms: Adaptation experiences of Indonesian ISMA students abroad - Pravitha, Cattleya Wahyu; Pakdel, Mohammadreza; Putra, Octa Pratama (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2025)
This qualitative study employed a narrative-based thematic analysis to explore the adaptation experiences of five Indonesian ISMA students studying abroad. Drawing on participants’ reflective narratives, the study identified five major themes: Initial Cultural Shock, Academic Adjustment, Language Barriers and Opportunities, Social Integration, and Personal Growth and Reflection. Findings reveal that students initially faced cultural, academic, and social disorientation as they navigated unfamiliar educational systems, classroom dynamics, and intercultural norms. However, these early challenges gradually evolved into opportunities for meaningful learning, cross-cultural engagement, and personal transformation. The adaptation process was found to be dynamic and multidimensional, shaped by emotional resilience, social integration, and reflective self-awareness. The study concludes that studying abroad is not merely an academic pursuit but a transformative journey that fosters intercultural competence, self-efficacy, and global-mindedness among Indonesian students.